Starch-Based Magnetic Nanocomposite for Targeted Delivery of Hydrophilic Bioactives as Anticancer Strategy - Casagrande-Denardin, J; Melo-Freire, R (Elsevier Ltd, 2021)
Magnetic nanocomposites were synthesized for the targeted delivery of hydrophilic bioactives through guidance generated by a magnetic field. Superparamagnetic iron oxide nanoparticles (SPIONs) were used to generate hydroxyethyl starch magnetic nanocapsules (HES MNCs). This synthesis allowed the co-encapsulation of oncocalyxone A (onco A) and surface-modified magnetite nanoparticles (Fe3O4@citrate) into the same nanostructure. The synthesized nanocapsules exhibited a core-shell morphology, with an average diameter of 143 nm. This nanocomposite showed potential anticancer activity (IC50) against four human tumor cell lines: glioblastoma SNB-19 (1.010 μgmL−1), colon carcinoma HCT-116 (2.675 μgmL−1), prostate PC3 (4.868 μgmL−1), and leukemia HL-60 (2.166 μgmL−1). Additionally, in vivo toxicity and locomotor activity were evaluated in a zebrafish (Danio rerio) model. The nanocomposite exhibited in vitro cytotoxicity, prolonged drug release profile and also responded to an applied magnetic field, representing a versatile compound with perspectives for highest concentration of different hydrophilic bioactives in a target tissue through magnetic vectorization. © 2021 Elsevier Ltd